Secure collaborations over message boards. (7th September 2006) - Ramkumar, Mahalingam; Memon, Nasir
We provide a message board model for collaborative systems, and propose an architecture and protocol for securing collaborative applications over message boards. The proposed architecture employs only efficient symmetric cryptographic principles, and low complexity trust modules with each participant. The trust modules are used to protect group secrets and reduce susceptibility to denial of service attacks. We outline an architecture and elements of a protocol for Secure Collaborations over Message Boards (SCMB). The SCMB protocol can serve as a foundation over which a wide range of collaborative applications can be realised.